1985
DOI: 10.1088/0031-9120/20/6/009
|View full text |Cite
|
Sign up to set email alerts
|

Charged poles?

Abstract: A significant portion of the recent work in the field of physics education research has been concerned with the identification of alternate conceptions (Driver and Easley, 1978) that students have about physical systems. Most of this work has been concentrated in the area of mechanics. There has been some work done in the area of electricity and magnetism but, by comparison, this area has received relatively little attention. The author reports on a study designed to determine if student difficulties in unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1
4

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 7 publications
4
24
1
4
Order By: Relevance
“…For example, Maloney showed that when asked to describe the force experienced by a charged particle near a magnetic pole, students answered that the particle will experience a force directed toward or away from the pole, even after instruction in magnetism. 7 There are several reasons for these answers, including the beliefs that magnets attract nearby objects, 8 magnets carry a net electrostatic charge in their poles, 8,9 and charged particles, whether stationary or moving, are the source of magnetic fields. 9 When magnetism is discussed in terms of field lines and magnetic poles are no longer explicitly discussed, a connection to electricity might still be present because students often confuse electric and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Maloney showed that when asked to describe the force experienced by a charged particle near a magnetic pole, students answered that the particle will experience a force directed toward or away from the pole, even after instruction in magnetism. 7 There are several reasons for these answers, including the beliefs that magnets attract nearby objects, 8 magnets carry a net electrostatic charge in their poles, 8,9 and charged particles, whether stationary or moving, are the source of magnetic fields. 9 When magnetism is discussed in terms of field lines and magnetic poles are no longer explicitly discussed, a connection to electricity might still be present because students often confuse electric and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, one participant answered on the questionnaire that magnets carry 'pole charges', while another stated that magnets attract certain materials because 'unlike charges attract each other while like charges repel each other'. This confused conception seems to occur commonly among students (Maloney, 1985;Borges et al, 1998;Guisasola et al, 2004).…”
Section: Results and Findingsmentioning
confidence: 99%
“…With regard to basic electricity and magnetism, Maloney (1985) revealed the confused conception that magnetic poles are charged and consequently attract or repel electric charges, in the same way as electrically charged rods would do. Students also incorrectly reason that magnetic fields exert forces on both stationary and moving charges.…”
Section: Concept Confusionmentioning
confidence: 99%
“…En este ítem, en cuanto al error en la dirección, al parecer los estudiantes piensan en términos de las líneas de campo magnético que se dirigen del polo norte del imán de la izquierda al polo sur del imán de la derecha. Esta concepción alternativa se relaciona con que los alumnos consideran que los polos magnéticos están cargados, el polo sur con carga negativa y el polo norte con carga positiva; por lo tanto la carga prueba positiva sería atraída al polo sur (Maloney, 1985). El argumento de que los estudiantes tienen estas ideas de líneas de campo magnético y/o fuerzas entre cargas magnéticas sobre cargas eléctricas se refuerza observando que la segunda opción incorrecta más fuerte es la opción A, con un 23 % (aún mayor que el porcentaje de los alumnos que responden esta pregunta correctamente), en la cual la dirección mostrada tiene la dirección del campo magnético en ese punto.…”
Section: Dificultades En El Efecto De Carga Inducida: íTems 13 Y 14unclassified